Dentro de la selva tropical - Willow, Diane; Jacques, Laura (Watertown, MA : Charlesbridge, 1993)
Introduction to life on the Amazon rain forest.
Translation of: At home in the rain forest.
Keywords: Rain forest ecology; Rain forests -- Amazon River Region; Spanish language materials